Ca kāʺ luṃʺ krvayʻ rā naññʻʺ padesā = How to increase your word power in Burmese - Lha Saminʻ, 1923- (Great Collections Microfilming Project. John M. Echols Collection., 1969)
On the usage of Burmese words.